Complementary Embryonic and Adult Cell Populations Enhance Myocardial Repair in Rat Myocardial Injury Model - Sergio Li Calzi; Todd Cook; Domenico G. Della Rocca; Juan Zhang; Vinayak Shenoy; Yuanqing Yan; Andrew Espejo; Anandharajan Rathinasabapathy; Max H. Jacobsen; Tatiana Salazar; George E. Sandusky; Lynn C. Shaw; et al. (Stem Cells International)
We compared the functional outcome of Isl-1+ cardiac progenitors, CD90+ bone marrow-derived progenitor cells, and the combination of the two in a rat myocardial infarction (MI) model. Isl-1+ cells were isolated from embryonic day 12.5 (E12.5) rat hearts and expanded in vitro. Thy-1+/CD90+ cells were isolated from the bone marrow of adult Sprague-Dawley rats by immunomagnetic cell sorting. Six-week-old female Sprague-Dawley rats underwent permanent left anterior descending (LAD) coronary artery ligation and received intramyocardial injection of either saline, Isl-1+ cells, CD90+ cells, or a combination of Isl-1+ and CD90+ cells, at the time of infarction. Cells were delivered transepicardially to the peri-infarct zone. Left ventricular function was assessed by transthoracic echocardiography at 1- and 4-week post-MI and by Millar catheterization (-dP/dt and +dP/dt) at 4-week post-MI. Fluorescence in situ hybridization (Isl-1+cells) and monochrystalline iron oxide nanoparticles labeling (MION; CD90+ cells) were performed to assess biodistribution of transplanted cells. Only the combination of cells demonstrated a significant improvement of cardiac function as assessed by anterior wall contractility, dP/dt (max), and dP/dt (min), compared to Isl-1+ or CD90+ cell monotherapies. In the combination cell group, viable cells were detected at week 4 when anterior wall motion was completely restored. In conclusion, the combination of Isl-1+ cardiac progenitors and adult bone marrow-derived CD90+ cells shows prolonged and robust myocardial tissue repair and provides support for the use of complementary cell populations to enhance myocardial repair.